Green removal of pyridine from water via adsolubilization with lignosulfonate intercalated layered double hydroxide - Mengqi Xia; Cheng Jin; Xianggui Kong; Meihong Jiang; Deqiang Lei; Xiaodong Lei (Adsorption Science & Technology)
In this work, lignosulfonate intercalated Mg 2 Al layered double hydroxide was fabricated by coprecipitation method, which was used as a functional adsorbent for removing pyridine from wastewater. The X-ray powder diffraction and Fourier transformed infrared were carried out to investigate the structure of the product. In the removal process, the as-prepared lignosulfonate intercalated Mg 2 Al layered double hydroxide sample exhibited good adsolubilization property for pyridine, with maximum capacity of 400.8 mg g −1 in initial pyridine concentration of 400 mg/l and the removal percentage achieved about 87.9%. In addition, the influence of pH, time, and initial concentration of pyridine on the adsorption capacity was also examined. Moreover, the adsorption kinetic followed the pseudo-second-order model. Furthermore, after regeneration, the adsorbent can still show high adsorption capacity even for 10 cycles of desorption–adsorption. It hoped that lignosulfonate intercalated Mg 2 Al layered double hydroxide can be used as adsorbent for the removal of organic pollutants in wastewater.